Islam, Ethics and Civilization - Omer, Spahic (Dar Al Wahi Publication, 2021)
This book critically examines the relationship between the Islamic worldview, ethics and civilization. It has nineteen chapters, each chapter accounting for a vital issue featured in the triad. Some of the themes discussed are: the problematic nature of the concept of civilization; the extent of the compatibility between Islamic and Western civilization; the problematic nature of the concept of architecture and the actual meaning of Islamic architecture; Islamization of knowledge; business ethics; moral values; Islamic piety; extra-terrestrial life and space exploration; agnosticism; and steps towards reinterpreting history. The book aims to ask more questions than to give answers. It adopts the principle that right questions are more important than average and unconvincing answers. While the former stimulates and opens new vistas in knowledge pursuits, the latter stultifies the mind and inhibits learning. Moreover, the former is open-ended and budding, the latter unyielding and frustrating. Indeed, as long as there are duly asked right questions, right answers are forthcoming, sooner rather than later. Therefore, the book is likewise intended to be at once a stimulus and a small contribution to the provision of answers. Some of the answers entailed in the book are rather qualified and intriguing. Positively, they are meant to be as such, to serve as eye-openers and even epiphanies. They invite other researchers and scholars to take up a similar approach and make contributions in their own fields and from their own perspectives. The book thus can be seen as a platform upon which an edifice of integrated knowledge can be built. That is crucial because Islam is the religion of spiritual certainty, ethical refinement, and “civilizational” awareness, as well as progress. They all converge in the province of man’s total being, in order to facilitate the self-actualization of his in his capacity as the vicegerent on earth. However, so much has happened in history in general, and in Muslim history in particular, that many aspects of the existential mission and purpose of man have been compromised, sometimes more and sometimes less. Hence, calls for purifying and Islamizing the essential aspects of human - together with Muslim - history, knowledge and civilization, grow louder. This book signifies one such call.